WE CAN WORK IT OUT - THE GLOBALISATION OF ICT-ENABLED SERVICES - Desiree van Welsum Xavier Reif (NATIONAL BUREAU OF ECONOMIC RESEARCH Working Paper 12799, 2006)
This paper examines the relationship between the share of employment potentially affected by offshoring and economic and structural factors, including trade in business services and foreign direct investment (FDI), using simple descriptive regressions for a panel of OECD economies between 1996 and 2003. It tests whether there are differences in the factors driving the shares of potentially offshorable "non-clerical" and clerical occupations in total employment. The results show a positive statistical association between the share of both "non-clerical" and clerical occupations potentially affected by offshoring and exports of business services, and a negative association with imports of business services. However, the results also show important differences between different types of occupations as they behave differently over time, and are affected differently by variables included in the model. In particular, net utwardmanufacturing FDI, ICT investment, and the relative size of the services sector all have a positive association with the share of potentially offshorable "non-clerical" cupations, but are negative with clerical occupations. Union density has a positive statistical association with clerical occupations but negative with "non-clerical" occupations. These results have important implications for policy, as they clearly suggest that different factors are driving the performance of different occupational groups.